Impacts of crop type, management and soil quality indicators on background nitrous oxide emissions (BNE) from Chinese croplands: a quantitative review and analysis. Issue 4 (1st June 2022) - Abdalla, Mohamed; Shang, Ziyin; Espenberg, Mikk; Cui, Xiaoqing; Mander, Ülo; Smith, Pete
Abstract : Crop types have significant impacts ( p < 0.05) on the background nitrous oxide emissions (BNE) from soils. The annual BNE for China when considering the proportion of planting area is 0.69 ± 1.52 kg N–N2 O ha −1 . Abstract : N2 O emissions (BNE) represents emissions from unfertilised soils during the current growing season or year and these contribute to total N2 O emissions. In this quantitative review and analysis, we collected 146 papers reporting BNE from 378 arable crop sites across China. The main aims were to estimate the BNE from Chinese cropland soils and to assess impacts of crop type, management and soil quality indicators on BNE. Data on sites, crops, management and soil quality indicators were collected. The data were segregated into cereal crops, rice and vegetables, and yield- and area-scaled BNE were calculated. The daily and annual BNE values (mean ± standard deviation) for cereals, rice and vegetables are 1.32 ± 1.16, 3.64 ± 3.84 and 10.68 ± 16.22 g N2 O–N ha −1 and 0.98 ± 0.83, 1.11 ± 0.49 and 2.86 ± 2.33 kg N–N2 O ha −1, respectively. Crop types have significant impacts ( p < 0.05) on the BNE values from soils. The overall mean annual BNE for China, considering the proportion of planting area for each crop type, is 0.69 ± 1.52 kg N–N2 O ha −1 . The total national mean annual BNE for China is 146 ± 109 Gg N2 O–N. The BNE from different crop types is variably controlled by interactions of many factors but primarily by soil quality indicators ( i.e. pH, soil N, soil C), climate and management. To reduce uncertainty in the total N2 O emissions from Chinese croplands, we suggest estimating the BNE at a national level, rather than using the default value of the Intergovernmental Panel on Climate Change (IPCC) of 1 kg N2 O–N ha −1 .